Some bacterial observations in frozen pork sausage. - Hendrickson, R.L. (Kansas Agricultural Experiment Station, 2012)
The preservation of food by freezing depends upon retarding the rate of microbial, enzymatic, and chemical changes. It is generally agreed that meat and meat products should be sharp-frozen at -10°F. (-23.3°C), and stored at 0 ̊ F. (-17.8°C) or lower to retard such changes. Work conducted by the Kansas Agricultural Experiment Station indicates that the quality of fresh pork is preserved for a longer period when frozen and stored at the lower temperature. The general usage of locker plants by individual families, for the storage of perishable products such as meat, poultry, fruits and vegetables, represents one of the most recent developments in the field of food distribution and preservation.
Keywords: Meat; Bacteria; Frozen pork sausage